PERAN EKONOMI KREATIF MELALUI UMKM DALAM MEWUJUDKAN PARIWISATA BERKELANJUTAN DI KECAMATAN BAHOROK - Rizkia Zahra Harahap; Hotbin Hasugian (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The research conducted discussed the role of the creative economy through UMKM in realizing sustainable tourism in Bahorok District. This research is a qualitative research, namely a type of research whose findings are not obtained through statistical procedures or other forms of calculation. The method used in this research is library research, namely a series of activities related to library data collection methods, reading and recording and processing research materials. The results of the research conducted show that the creative economy through UMKM contributes to realizing sustainable tourism in Bahorok District, the creative economy provides opportunities for individuals to generate added value through works and contributes to economic growth. The creative economy and tourism can create mutually beneficial synergies and create a positive economy and increase the attractiveness of an area as a tourist destination by utilizing the uniqueness of local culture and creativity. Apart from that, there are also several ways to support sustainable tourism through a creative economy that is managed through MSMEs, namely: 1) Promotion of local culture; 2) Development of local products and services; 3) Innovation and Collaboration; 4) Increased participation of local communities; 5) Homestay and local accommodation; and 6) Environmental preservation. Keywords:. Creative Economy, UMKM, Sustainable Tourism